Bioremediation of Nickel and Iron from Solutions by Viable, Killed and Immobilized Microorganisms - Elizabeth, K.M.; Begum, Arshiya (Asian Journal of Chemistry, 2010)
Bioremediation of heavy metals such as nickel and iron from artificially introduced solutions was tested. The microorganisms used in this study were Bacillus (BS5), Nitrosomonas, Bacillus (BS6) and Pencillium species. The metal ion concentration used was 100 mg/L. The bioremediation of these metals by live, killed and immobilized microorganisms was assessed. The sorbent concentration used was 5 mg/mL. There was highest percentage removal of Ni (92.5%) and Fe (92.2%) by viable Nitrosomonas species, indicating that it was a very potential microbe. Biosorption technique showed 20.8-84% removal of Ni and 65.7-100% removal of Fe by microorganisms used. There was 92.6% removal of Ni by Bacillus species and 97.8% by Penicillium species through immobilization technique. The effect of pH on bioremediation of these metals was also assessed. The results obtained were subjected to chisquare test and indicate that all the microorganisms and techniques used were efficient in the removal of Ni and Fe and can be used to remediate these metals from industrial, agricultural and domestic wastewaters.